1988
DOI: 10.1016/0014-5793(88)80169-8
|View full text |Cite
|
Sign up to set email alerts
|

Effects of long‐chain N‐acylethanolamines on lipid peroxidation in cardiac mitochondria

Abstract: A long-chain N-acylethanolamine (N-oleoyl-2-aminoethanol) is shown to inhibit the production of thiobarbituric acidreactive substances in rat heart mitochondria treated with Fe?+ or Fe'+/ADP. The inhibition is concentration-dependent in the range X%150 PM of the agent and can be nearly complete depending on the type and amount of the free radicalgenerating system. Structural analogues of N-acylethanolamine are inhibitory as well, but neither oleic acid nor ethanolamine has measurable effects. N-Oleoyl-2-aminoe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

1993
1993
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(7 citation statements)
references
References 15 publications
0
7
0
Order By: Relevance
“…Since PEA is produced by the brain following ischaemic insult [22], the authors suggested that this compound may act as an endogenous neuroprotective agent. The authors further reported that anandamide not only afforded no isolated rat heart mitochondria with FeSO 4 or FeCl 3 / ADP [86]. Another possibility is that protective effects of AEA and possibly PEA that are more relevant to the situation in vivo may be seen if cAMP levels are raised during the exposure periods [87].…”
Section: Ischaemiamentioning
confidence: 91%
“…Since PEA is produced by the brain following ischaemic insult [22], the authors suggested that this compound may act as an endogenous neuroprotective agent. The authors further reported that anandamide not only afforded no isolated rat heart mitochondria with FeSO 4 or FeCl 3 / ADP [86]. Another possibility is that protective effects of AEA and possibly PEA that are more relevant to the situation in vivo may be seen if cAMP levels are raised during the exposure periods [87].…”
Section: Ischaemiamentioning
confidence: 91%
“…Among NAEs, OEA, PEA, and AEA appeared to inhibit Cu 2+ -induced in vitro lipid peroxidation in plasma lipoproteins [ 202 ] and cardiac mitochondria [ 207 ], consequently showing antioxidant properties in the pathogenesis of atherosclerosis. Moreover, Zolese and collaborators demonstrated that, depending on its concentration of incubation, PEA exerts both anti-oxidative and pro-oxidative effects on radical-induced oxidation of plasma LDL [ 208 ].…”
Section: Modulation Of Oxidative Stress and Lipid Peroxidation Thrmentioning
confidence: 99%
“…Moreover, OEA and PEA appeared to inhibit Cu 2+ -induced in vitro lipid peroxidation of plasma lipoproteins 12 and cardiac mitochondria. 61 All these evidences could contribute to explain the increase of lag time and the decrease of Ox-LDL found in this clinical trial.…”
Section: Discussionmentioning
confidence: 59%